Achieving teaching quality in Sub-Saharan Africa : empirical results from cascade training - Lange, Sarah; Benavot, Aaron (Wiesbaden : Springer, 2016)
Sarah Lange examines the effectiveness of cascade training, which constitutes a cost-effective training model in teacher training. In development cooperation countries, teaching quality is expected to improve with teacher professional development; for this purpose, she explores the effectiveness of training multipliers in schools in Cameroon. This research question is analysed with a design, which encompasses a questionnaire survey provided to teachers, students and principals as well as a teacher video survey and a student achievement test. The empirical results show the effects of cascade training on the learner-oriented teaching practice, if the trained teachers are supported in their role as change agents. Among the conditions for the conceptual quality and the implementation of cascade training, the continuity of school-based professional development is particularly emphasized in light of the results.
Keywords: FORMACIÓN PROFESIONAL DE MAESTROS -- CAMERÚN; EDUCACIÓN COMPARADA -- CAMERÚN; EDUCACION INTERNACIONAL; ENSEÑANZA -- CAMERÚN